50.4k views
5 votes
Simplify the following:

Simplify the following:-example-1

1 Answer

3 votes

First, we can bring both fractions under the common denominator (a - 3)(a - 5):


(4)/(a-3)\Big((a-5)/(a-5)\Big) +(9)/(a-5)\Big((a-3)/(a-3)\Big)\\\\=(4(a-5)+9(a-3))/((a-3)(a-5))

Looking at the numerator, we can distribute and collect like terms:


4(a-5)+9(a-3)=4a-20+9a-27=13a-47

and looking at the denominator, we can do the same:


(a-3)(a-5)=(a-3)a+(a-3)(-5)\\=a^2-3a-5a+15\\=a^2-8a+15

With these simplified expressions, the final fraction becomes


(13a-47)/(a^2-8a+15)

User Malachi
by
5.0k points